ADEQUATE FUNDING PANACEA FOR DEVELOPMENT OF GREEN CURRICULUM FOR NIGERIAN SCHOOLS - Kayode, Olofinkua Vincent; Ndidiamaka, Nnorom Jane; Mohammed, Ahmed (Antis Publisher, 2024)
This paper examined the important for funding green curriculum in the Nigerian schools for effective implementation. Secondary data were employed in the paper. The data were collected from print and online publications. Content analysis was used to select and limit the literatures to the minimum size. The paper concluded that adequate funding is key in the realization of green curriculum objectives in the schools. Adequate funding of green curriculum in the schools will support smooth planning of green curriculum, aid employment of green curriculum expertise, ensure effective training and retraining, smooth implementation of green curriculum and supervision of green curriculum in Nigerian schools. Based on this findings, the paper recommends that the government should provide special funding window for the funding of green school programme especially the curriculum component aspect of the programme.